The Treatment : The Story of Those Who Died in the Cincinnati Radiation Tests - Stephens, Martha (Book collections on Project MUSE., 2002)
A revealing expose on extreme radiation experiments performed on unknowing cancer patients during the 1960s which caused their deaths.